2007
DOI: 10.2176/nmc.47.409
|View full text |Cite
|
Sign up to set email alerts
|

Recording of Corticospinal Evoked Potential for Optimum Placement of Motor Cortex Stimulation Electrodes in the Treatment of Post-stroke Pain -Two Case Reports-

Abstract: The corticospinal motor evoked potential (MEP) evoked by motor cortex stimulation was investigated as an intraoperative index for the placement of stimulation electrodes in the epidural space over the motor cortex for the treatment of post-stroke pain. A grid of plate electrodes was placed in the epidural space to cover the motor cortex, sensory cortex, and premotor cortex employing a magnetic resonance imaging-guided neuronavigation system in two patients with severe post-stroke pain in the right extremities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The amplitude of the muscle response (D-wave) is measured. 52,53 Previous studies have specifically examined D-wave amplitude changes and have shown that a 50% decrease reliably predicts postoperative motor deficit. 36 While informative, D-waves are not perfect.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of the muscle response (D-wave) is measured. 52,53 Previous studies have specifically examined D-wave amplitude changes and have shown that a 50% decrease reliably predicts postoperative motor deficit. 36 While informative, D-waves are not perfect.…”
Section: Discussionmentioning
confidence: 99%
“…described in two patients the D-wave of the MEP as an intraoperative indicator for the placement of stimulating electrodes over the motor cortex for pain relief, the percentage VAS reduction was significantly correlated with the D-wave amplitude, indicating that D-wave recording provides and intraoperative guide for placing the stimulating electrode at the optimum position on the motor cortex. [124]…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the D-wave of corticospinal MEP reflects impulses arising from the direct activation of the axons of corticospinal tract neurons, and the D-wave is recorded only when the primary motor cortex is stimulated [19][20][21]25] . Unlike muscle responses to motor cortex stimulation, the D-wave is resistant to surgical doses of anesthetics and is unaffected by muscle relaxants, apart from changes in the excitability of spinal motoneurons, and it is easy to compare the amplitudes related to the site of cortical stimulation [19][20][21][25][26][27] . On the basis of these findings, we carried out D-wave monitoring to select the best location of the stimulation electrode in this study.…”
Section: Discussionmentioning
confidence: 99%
“…How to place the cortical stimulating electrode is also important in MCS therapy. Various surgical techniques for the accurate placement of epidural electrodes over the motor cortex have been reported [3,6,11,19] . For the placement of epidural electrodes, a structural and functional magnetic resonance brain imaging (MRI and fMRI, respectively) procedures were used in the multicenter studies to verify the anatomical location of the stroke and to identify the cortical area of functional activation ipsilateral to the stroke within the primary motor cortex that is associated with the voluntary movement of the affected hand [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation